A single dose of exenatide had no effect on blood flow velocity in the middle cerebral artery in elderly healthy volunteers: Randomized, placebo-controlled, double-blind clinical trial - Ölmestig, Joakim; Marlet, Ida R.; Vilsbøll, Tina; Rungby, Jørgen; Rostrup, Egill; Lambertsen, Kate L.; Kruuse, Christina (Frontiers in Aging Neuroscience, 2022)
Background and aims Glucagon-like peptide 1 (GLP-1) receptor agonists (GLP-1RA) are widely used for the treatment of type 2 diabetes, and recent studies indicate that they may be cardio- and neuroprotective. The safety and effect of a single dose of exenatide, a short-acting GLP-1RA, on cerebral and peripheral arterial function remain unknown. Methods In this randomized, double-blind pilot trial, we assigned elderly healthy volunteers without diabetes and no previous history of stroke to receive a single dose of subcutaneous exenatide (5 µg) or placebo. Primary outcome was immediate changes over time in blood flow velocity of the middle cerebral arteries (VMCA) assessed by repeated transcranial Doppler measurements. Secondary outcomes were changes in peripheral arterial function with finger plethysmography, ankle-brachial index (ABI), and inflammatory- and endothelial-specific biomarkers. Results Healthy volunteers (13 women and 17 men) were included: (mean ± standard deviation) age: 62 ± 8 years; body weight: 79.6 ± 12.7 kg; VMCA: 65.3 ± 10.7 cm/s; fasting plasma glucose: 5.5 ± 0.5 mmol/l; HbA1c: 33.9 ± 4.1 mmol/mol (5.3 ± 0.38 %). No differences between exenatide and placebo group were seen regarding VMCA (p=0.058), systolic ABI (p=0.71), plethysmography (p=0.45), tumor necrosis factor (p=0.33), interleukin-6 (p=0.11), interleukin-1β (p=0.34), vascular cell adhesion molecule 1 (p=0.73), intercellular adhesion molecule 1 (p=0.74), or E-selectin (p=0.31). No severe adverse events were observed. Conclusions A single dose of exenatide did not change cerebral blood flow velocity or peripheral vessel function in elderly healthy volunteers. The medication was safe to use in persons without diabetes allowing us to investigate this drug further in search of the neuroprotective mechanisms.